THE INFLUENCE OF JOB-ORGANIZATIONAL FIT, JOB-DESCRIPTION, AND EMPLOYEE COMPETENCE ON EMPLOYEE PERFORMANCE AT MULYOREJO POLICE STATION - sari, Alviani sukma widya; Sutarmin (MSJ : Majority Science Journal, 2025)
The concept of employee performance in the police institution is very important to ensure effectiveness and efficiency in carrying out tasks related to security and public services. Focusing organizational efforts and strategies on employee performance is a strategic step in creating a more professional, transparent, and accountable police force, which will ultimately strengthen stability and security in society. This study then aimed to determine the influence of various factors that can improve personnel performance in the police institution, including job-organizational fit, job descriptions, and employee competencies. This study used a quantitative approach based on the positivism paradigm. The study was conducted on employees at the Mulyorejo Police Sector Office (Polsek), Surabaya City. The number of samples determined was 54 employees who were determined using a saturated sampling technique. The research data that had been collected using a questionnaire mechanism were then analyzed using multiple linear regression analysis, using control variables including gender and marital status. The results of the study showed that: a) job-organizational fit had a positive and significant effect on personnel performance; b) job description had a positive and significant effect on personnel performance; c) employee competencies had a positive but not significant effect on personnel performance; d) simultaneously, job- organizational fit, job description, and employee competency had a positive and significant effect on personnel performance, and; e) job description was proven to be a dominant variable in influencing personnel performance at the Mulyorejo Police Sector Office (Polsek), Surabaya City which determined as the research sample.